Emotional intelligence for managing results in a diverse world : the hard truth about soft skills in the workplace - 215113 Gardenswartz, Lee; Cherbosque, Jorge, 1955-; Rowe, Anita, 1946- (Mountain View, CA : Davies-Black Publishing, 2008)
36